Temperature dependence of resonance characteristics of silicon resonators and thermal stability improvement by differential operation method. (21st March 2017) - Sana, Amrita Kumar; Jun, Maeda; Yokoyama, Shuhei; Amemiya, Yoshiteru; Yokoyama, Shin
Abstract: In this paper, we describe the mechanism and solution for dominating temperature effects on refractive-index-based Si optical resonator sensors such as ring resonator and photonic crystal resonator sensors. The temperature change affects the silicon refractive index and also the resonator mechanical shape. As a result, it is reported that the refractive index change is marked, whereas the mechanical deformation effect is negligible. We also demonstrated that the differential operation is effective for suppressing the temperature effect for Si ring resonator sensors.